(untitled) (Nordic Journal of African Studies, 2010)
Archaeological excavations in southern Africa have yielded a wide variety of small clay figurines, the origins of which have been traced back to early farming communities. Whereas many of these artefacts are fairly naturalistic in appearance, others clearly are not. The purpose of this essay is to explore the social significance of one of the stylized figurine types, an intriguing phallic-shaped female representation. Ever since Summers completed the first systematic figurine study in 1957, interpretive efforts of art historians, archaeologists and anthropologists have focused on the concept of fertility. This paper argues that the fertility paradigm, far from being irrelevant, has remained poorly defined. Moreover, it has produced an understanding that is tainted by a masculine bias, and does not do justice to the conceptual originality of the icon. An alternative reading of fertility is proposed, in which a symbolic war between the sexes features centrally.